تقويم إدارة النشاط الرياضي الخارجي لكليات جامعة صلاح الدين : من وجهة نظر مدربي الألعاب الرياضية - عولا، سرتيب عمر; مصطفى، ديار خليل (جامعة صلاح الدين, 2014)
يهدف البحث الحالي إلى 1- التعرف على إدارة النشاط الرياضي الخارجي لكليات جامعة صلاح الدين من وجهة نظر مدربي الألعاب الرياضية. 2- التعرف على مجالات إدارة النشاط الرياضي الخارجي لكليات جامعة صلاح الدين من وجهة نظر مدربي الألعاب الرياضية. تم استخدام المنهج الوصفي بالأسلوب المسحي لملاءمته وطبيعة البحث، واشتملت العينة على مدربي الألعاب الرياضية في كليات جامعة صلاح الدين من حملة شهادة البكالوريوس في التربية الرياضية والبالغ عددهم (٢١) فردا واختبارها بواسطة استمارة استبيان معد من قبل الباحثين إذ تكونت من(48) فقرة تقيس سبعة مجالات هي (خطة برنامج النشاط الرياضي الخارجي، الميزانية، الإمكانيات والتجهيزات الرياضية، اللجان المساعدة، الحوافز، عوامل الأمن والسلامة، التدريب)، تمت معالجة البيانات احصائيا باستخدام الوسط الحسابي، الانحراف المعياري، النسبة المئوية، المتوسط الفرضي، معامل (ألفا) لكرونباك لحساب الثبات، اختبار التائي لعينة واحدة، واستنتج الباحثان ما يأتي: 1- حصلت كليات جامعة صلاح الدين على مستوى إيجابي وبفروق معنوية في إدارة النشاط الرياضي الخارجي من وجهة نظر مدربي الألعاب الرياضية. 2- ظهرت فروق معنوية بين المجالات الثلاثة (خطة برنامج النشاط الرياضي الخارجي، اللجان المساعدة، التدريب)، بينما جاءت بقية المجالات (الميزانية، الإمكانيات والتجهيزات الرياضية، الحوافز، عوامل الأمن والسلامة) غير معنوية. The current research aims at: 1- Recognition Management sporting activity outside Colleges of Salahaddin University From the perspective sports instructors. 2- Recognition the areas of management sports activity outside Colleges of Salahaddin University From the perspective sports instructors. Were used descriptive approach survey manner for suitability and the nature of the search, and sample included coaches sports in colleges Salahaddin University of holders of BA degree in Physical Education, totaling (21) individuals and tested by a questionnaire prepared by the researchers as it consisted of (48) items that measure seven areas ( program Plan sporting activity outside , the budget , the possibilities and sports equipment , the committees of assistance, incentives , safety and security factors , training) , were processed data statistically using the arithmetic mean , standard deviation , percentage, average hypothesis , coefficient (alpha) to calculate stability, T- test for one sample , and the researchers concluded: 1- I got the faculties of the University Salahuddin at the level of positive and significant differences in the management of physical activity outside of the point of view of sports instructors. 2- Significant differences were found between the three areas (Program Plan physical activity outside, the committees of assistance, training), while the rest came domains (budget, facilities and sports equipment, incentives, safety and security factors) were not significant.
Keywords: النشاط الرياضي -- الألعاب الرياضية -- الأهداف التربوية -- التقويم -- المدربون الرياضيون -- جامعة صلاح الدين ، العراق